A kind of TPE gloves and preparation method thereof
By using SEBS and surface-modified WCNFs materials, combined with micro-foam injection molding technology, the problems of uneven material flow and low yield in the production process of traditional TPE gloves are solved, and high-performance, environmentally friendly and lightweight TPE glove preparation is achieved.
Patent Information
- Application Number
- CN202510075664.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-17
AI Technical Summary
Traditional TPE gloves have problems such as uneven material flow and low yield during the production process, and the existing preparation methods have problems such as unstable product performance and single performance, which limits the large-scale production and wide application of TPE gloves.
TPE gloves are prepared by micro-foaming injection molding technology using SEBS as the substrate and surface-modified bio-based nanocellulose (WCNFs) as the main raw material. This method improves the dispersion and compatibility of nanocellulose through surface modification, and improves the mechanical properties and thermal insulation properties of the material through micro-foaming injection molding technology.
It significantly improves the mechanical properties, antibacterial properties, antistatic properties, thermal insulation properties and long-term stability of TPE gloves, while achieving environmental protection and lightweight, and is suitable for the preparation of high-performance protective gloves.
Smart Images

Figure SMS_9 
Figure SMS_10 
Figure SMS_11
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of TPE gloves, and in particular to a TPE glove and a preparation method thereof. Background Art
[0002] With the increasing awareness of environmental protection and the increasing requirements for health and safety standards, traditional PVC and latex gloves are gradually being eliminated due to their potential environmental impact and allergic risks. As a new type of environmentally friendly material, TPE (thermoplastic elastomer) has attracted widespread attention for its excellent physical properties, recyclability and non-toxicity. TPE is a polymer material that combines the characteristics of plastic and rubber. It shows the elasticity of rubber at room temperature and can be melted and processed like plastic at high temperature. Although TPE materials have many advantages, they still face some challenges in practical applications. For example, the production process of traditional TPE gloves may have problems such as uneven material flow and low yield, which limit the large-scale production and wide application of TPE gloves. In addition, the most commonly used methods for preparing TPE gloves are injection molding and blow molding, both of which have high production efficiency and relatively low equipment cost, but there are problems such as unstable product performance and single performance. Therefore, it is of great significance to develop an environmentally friendly, high-performance and stable TPE glove and its preparation method. Summary of the invention
[0003] In view of this, the present invention proposes a TPE glove and a preparation method thereof. The TPE glove is made of SEBS as a substrate, surface-modified bio-based nanocellulose (WCNFs) as a main raw material, and is prepared by micro-foam injection molding technology. It has excellent mechanical properties, antibacterial properties, antistatic properties, thermal insulation properties, long-term stability and environmental protection.
[0004] The technical solution of the present invention is achieved in this way:
[0005] The invention provides a TPE glove. The components of the TPE glove include, by weight, 100 parts of a base material, 5 parts to 15 parts of bio-based nanocellulose, 0.5 parts to 1 part of an antioxidant, and 1 part to 2 parts of a masterbatch raw material.
[0006] On the basis of the above technical scheme, preferably, the substrate is one of SBS, SEBS, TPU, TPO, and TPV; the antioxidant is one of Irganox 1010, Irganox 1076, Irgafos 168, butylated hydroxytoluene, TNPP, and dilaurylthiopropionate; and the bio-based nanocellulose is wood cellulose nanocellulose WCNFs.
[0007] More preferably, the substrate is SEBS; the antioxidant is Irganox 1010; and the bio-based nanocellulose is surface-modified wood cellulose nanocellulose WCNFs.
[0008] On the basis of the above technical solution, preferably, the wood cellulose nanocellulose WCNFs are specifically surface-modified WCNFs, and the preparation steps are:
[0009] (1) After mixing the WCNFs suspension with the silver ion solution, a hydrochloric acid solution was added to adjust the pH to 4-5, and the stirring was continued to load the silver ions on the surface of the WCNFs; then the supernatant was removed by high-speed centrifugation, and the precipitate was washed and dispersed to obtain WCNFs loaded with silver nanoparticles;
[0010] (2) mixing the silver nanoparticle-loaded WCNFs with a conductive polymer solution and an initiator, and starting a polymerization reaction to coat the conductive polymer on the surface of the WCNFs; then centrifuging at high speed to remove the supernatant, washing the precipitate, and dispersing to obtain modified WCNFs;
[0011] (3) Baking the modified WCNFs at low temperature until they are completely dry to obtain surface-modified WCNFs.
[0012] On the basis of the above technical solution, preferably, the ratio of the mass of the WCNFs suspension to the volume of the silver ion solution is 1:10-20, and the concentrations of the WCNFs suspension and the silver ion solution are both 1 wt%-1.5 wt%.
[0013] On the basis of the above technical scheme, preferably, the ratio of the mass of the WCNFs loaded with silver nanoparticles to the volume of the conductive polymer solution and the initiator is 1:10-20:2-3; the concentration of the WCNFs loaded with silver nanoparticles is 1wt%-1.5wt%; the conductive polymer solution is a polypyrrole solution with a concentration of 1wt%-1.5wt%; and the initiator is ammonium persulfate with a concentration of 0.1M.
[0014] The present invention also provides a method for preparing the TPE gloves, which comprises the following steps:
[0015] (1) Drying the substrate, bio-based nanocellulose, antioxidant and masterbatch raw materials at low temperature to remove excess water;
[0016] (2) Mixing the dried substrate and bio-based nanocellulose evenly, adding antioxidants and masterbatch raw materials and mixing evenly again;
[0017] (3) melt-extruding the uniformly mixed components to prepare composite material particles;
[0018] (4) preparing a glove sample by using the composite material particles using micro-foam injection molding technology;
[0019] (5) The glove sample is smoothed and cured by ultraviolet light to obtain a TPE glove.
[0020] Based on the above technical solution, preferably, in step (1), the low-temperature drying temperature is 60°C-80°C, and the drying time is 4 hours-6 hours.
[0021] On the basis of the above technical solution, preferably, in the step (2), the mixing is carried out in a high-speed mixer, the rotation speed of which is 1000 rpm-1500 rpm, and the mixing time is 8 minutes-12 minutes.
[0022] On the basis of the above technical solution, preferably, in the step (3), the melt extrusion is carried out by a twin-screw extruder, and the extrusion parameters are set as follows: barrel temperature: 160°C-180°C; screw speed: 80 rpm-100 rpm; extrusion rate: 4 kg / h-5 kg / h.
[0023] On the basis of the above technical solution, preferably, in the step (4), the parameters of the micro-foam injection molding technology are set as follows: barrel temperature: 180°C-200°C; mold temperature: 40°C-50°C; injection pressure: 80 MPa-100 MPa; holding time: 15 seconds-20 seconds; injection speed: 50 mm / s-80 mm / s; foaming agent: supercritical carbon dioxide, the addition amount is 1%-3% of the weight of the composite material.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The bio-based nanocellulose used in preparing gloves of the present invention is surface modified to further improve the dispersibility and compatibility of nanocellulose, so that it is more evenly distributed in the composite material, thereby significantly improving the mechanical properties of the prepared gloves, and also improving the thermal stability and chemical stability of nanocellulose, which is suitable for the preparation of high-performance protective gloves, such as industrial protective gloves, high-temperature working gloves, etc., and the material has good biodegradability and environmental friendliness, and is suitable for gloves that need to meet environmental protection standards. In addition, surface modification can give nanocellulose multiple functions such as antibacterial and antistatic properties, which can not only simplify the formula and reduce costs, but also improve the comprehensive performance and scope of application of the gloves.
[0026] 2. The present invention adopts micro-foam injection molding technology to prepare TPE gloves, which can form a synergistic effect with surface-modified WCNFs, thereby significantly improving the comprehensive performance of TPE gloves, specifically:
[0027] (1) Surface-modified WCNFs have high crystallinity and high mechanical strength, as well as good dispersibility and compatibility, which can significantly improve the mechanical properties of the TPE substrate and are evenly distributed in the TPE substrate. Micro-foam injection molding can reduce the density of the material by introducing tiny bubbles, while maintaining or even improving the mechanical properties of the material. The presence of tiny bubbles can reduce stress concentration and improve the toughness and impact resistance of the material. At the same time, the formation and growth of bubbles can further promote the uniform dispersion of surface-modified WCNFs in the substrate, ensuring the consistency of the overall performance of the material.
[0028] (2) Microfoam injection molding can significantly reduce the density of the material and achieve lightweight, which is very important for improving the wearing comfort and flexibility of gloves. The presence of bubbles can improve the thermal insulation performance of the material and reduce heat transfer. The surface-modified WCNFs have good thermal and chemical stability and can maintain their performance during the microfoaming process, further improving the thermal insulation performance of the material, thereby preventing the material from being degraded by high temperature or chemical environment.
[0029] (3) The surface-modified WCNFs loaded with silver nanoparticles and conductive polymers of the present invention have excellent antibacterial and conductive properties. The presence of bubbles can increase the surface area of the material and the connectivity of the conductive network, further improving the antibacterial and antistatic capabilities of the material.
[0030] Therefore, this synergistic effect not only improves the mechanical properties, antibacterial properties and antistatic properties of the gloves, but also achieves lightweight and environmental friendliness, and has important application value and market prospects. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1: Modification of lignocellulosic nanocellulose (WCNFs)
[0033] 1. Silver ion loading:
[0034] Take 5 g of WCNFs suspension (commercially available product, concentration is 1 wt%), add 100 mL of silver ion solution (concentration is 1 wt%), and stir on a magnetic stirrer for 1 hour to allow the silver ions to be evenly adsorbed on the surface of WCNFs; add 10 mL of hydrochloric acid (1 M) and adjust the pH value to 4-5 to promote the reduction reaction of silver ions; continue stirring for 1 hour to reduce the silver ions to silver nanoparticles and load them on the surface of WCNFs.
[0035] The WCNFs suspension loaded with silver nanoparticles was centrifuged at 8000 rpm for 10 minutes, and the supernatant was removed. The suspension was washed with deionized water and 95% ethanol for 3 times to remove the unadsorbed silver ions and residual hydrochloric acid. After the last wash, the modified WCNFs were redispersed in 100 mL of deionized water for later use.
[0036] 2. Conductive polymer loading:
[0037] Take 5 g of the WCNFs suspension loaded with silver nanoparticles in the previous step (concentration of 1 wt%), add 100 mL of polypyrrole solution (concentration of 1 wt%), and add 10 mL of ammonium persulfate (APS, 0.1 M) as an initiator to start the polymerization reaction; stir on a magnetic stirrer for 2 hours to evenly coat the polypyrrole on the surface of the WCNFs.
[0038] The polypyrrole-loaded WCNFs suspension was centrifuged at 8000 rpm for 10 minutes, and the supernatant was removed. The suspension was washed with deionized water and 95% ethanol for 3 times to remove the unadsorbed polypyrrole and residual ammonium persulfate. After the last wash, the modified WCNFs were redispersed in 100 mL of deionized water for later use.
[0039] 3. Drying:
[0040] The modified WCNFs suspension in the previous step was poured into a shallow dish and placed in an oven at 60°C for 24 hours until completely dried to obtain surface-modified WCNFs with antibacterial and antistatic properties.
[0041] Example 2: Modification of lignocellulosic nanocellulose (WCNFs)
[0042] 1. Silver ion loading:
[0043] Take 10 g of WCNFs suspension (commercially available product, concentration is 1 wt%), add 100 mL of silver ion solution (concentration is 1.5 wt%), and stir on a magnetic stirrer for 1 hour to allow the silver ions to be evenly adsorbed on the surface of WCNFs; add 10 mL of hydrochloric acid (1 M) and adjust the pH value to 4-5 to promote the reduction reaction of silver ions; continue stirring for 1 hour to reduce the silver ions to silver nanoparticles and load them on the surface of WCNFs.
[0044] The WCNFs suspension loaded with silver nanoparticles was centrifuged at 8000 rpm for 10 minutes, and the supernatant was removed. The suspension was washed with deionized water and 95% ethanol for 3 times to remove the unadsorbed silver ions and residual hydrochloric acid. After the last wash, the modified WCNFs were redispersed in 100 mL of deionized water for later use.
[0045] 2. Conductive polymer loading:
[0046] Take 5 g of the WCNFs suspension loaded with silver nanoparticles in the previous step (concentration of 1.5 wt%), add 100 mL of polypyrrole solution (concentration of 1 wt%), and add 15 mL of ammonium persulfate (APS, 0.1 M) as an initiator to start the polymerization reaction; stir on a magnetic stirrer for 2 hours to evenly coat the polypyrrole on the surface of the WCNFs.
[0047] The polypyrrole-loaded WCNFs suspension was centrifuged at 8000 rpm for 10 minutes, and the supernatant was removed. The suspension was washed with deionized water and 95% ethanol for 3 times to remove the unadsorbed polypyrrole and residual ammonium persulfate. After the last wash, the modified WCNFs were redispersed in 100 mL of deionized water for later use.
[0048] 3. Drying:
[0049] The modified WCNFs suspension in the previous step was poured into a shallow dish and placed in an oven at 60°C for 24 hours until completely dried to obtain surface-modified WCNFs with antibacterial and antistatic properties.
[0050] Example 3: Modification of lignocellulosic nanocellulose (WCNFs)
[0051] 1. Silver ion loading:
[0052] Take 5 g of WCNFs suspension (commercially available product, concentration of 1.5 wt%), add 100 mL of silver ion solution (concentration of 1 wt%), and stir on a magnetic stirrer for 1 hour to allow the silver ions to be evenly adsorbed on the surface of WCNFs; add 15 mL of hydrochloric acid (1 M) and adjust the pH value to 4-5 to promote the reduction reaction of silver ions; continue stirring for 1 hour to reduce the silver ions to silver nanoparticles and load them on the surface of WCNFs.
[0053] The WCNFs suspension loaded with silver nanoparticles was centrifuged at 8000 rpm for 10 minutes, and the supernatant was removed. The suspension was washed with deionized water and 95% ethanol for 3 times to remove the unadsorbed silver ions and residual hydrochloric acid. After the last wash, the modified WCNFs were redispersed in 100 mL of deionized water for later use.
[0054] 2. Conductive polymer loading:
[0055] Take 10 g of the WCNFs suspension loaded with silver nanoparticles in the previous step (concentration of 1 wt%), add 100 mL of polypyrrole solution (concentration of 1.5 wt%), and add 10 mL of ammonium persulfate (APS, 0.1 M) as an initiator to start the polymerization reaction; stir on a magnetic stirrer for 2 hours to evenly coat the polypyrrole on the surface of the WCNFs.
[0056] The polypyrrole-loaded WCNFs suspension was centrifuged at 8000 rpm for 10 minutes, and the supernatant was removed. The suspension was washed with deionized water and 95% ethanol for 3 times to remove the unadsorbed polypyrrole and residual ammonium persulfate. After the last wash, the modified WCNFs were redispersed in 100 mL of deionized water for later use.
[0057] 3. Drying:
[0058] The modified WCNFs suspension in the previous step was poured into a shallow dish and placed in an oven at 50°C for 24 hours until completely dried to obtain surface-modified WCNFs with antibacterial and antistatic properties.
[0059] Example 4: Preparation of modified TPE gloves
[0060] In this embodiment, the material of the TPE gloves is surface modified and micro-foam injection molding technology is used. The specific steps are as follows:
[0061] 1. Drying
[0062] 5 g of the surface-modified WCNFs prepared in Example 1, 100 g of styrene-ethylene / butylene-styrene block copolymer (SEBS), 0.5 g of antioxidant Irganox 1010, and 2 g of black masterbatch were placed in a drying oven and dried at 60° C. for 4 hours to remove any moisture that may be present.
[0063] 2. Material Mixing
[0064] Place the dried SEBS and surface-modified WCNFs in a high-speed mixer and mix at 1000 rpm for 10 minutes to ensure that all components are fully dispersed. Then add Irganox 1010 and black masterbatch and continue mixing for 10 minutes to ensure that all additives are evenly dispersed.
[0065] 3. Put the mixed materials into a twin-screw extruder, set the extrusion parameters, and perform melt extrusion to prepare composite material particles. The extrusion parameters are as follows:
[0066] Barrel temperature: 180°C; screw speed: 100 rpm; extrusion rate: 5 kg / h.
[0067] 4. Injection molding
[0068] (1) Set injection molding parameters:
[0069] Cylinder temperature: 180°C; Mold temperature: 40°C; Injection pressure: 100 MPa; Holding time: 15 seconds; Injection speed: 80 mm / s; Foaming agent: supercritical carbon dioxide ( ), the addition amount is 1% of the weight of the composite material.
[0070] (2) Micro-foam injection molding:
[0071] Put the prepared composite material particles into the hopper of the tape casting machine. Turn on the tape casting machine and preheat it to the set temperature to ensure that the barrel, nozzle and mold reach the required temperature; Connect the foaming device to the air inlet of the casting machine, making sure the connection is tight and leak-free. Foaming device, supercritical Injected into the composite particles. Control pressure and flow to ensure Evenly dispersed in the composite material. Start the casting machine and perform injection molding according to the set injection molding parameters. During the injection molding process, carbon dioxide will expand rapidly in the mold to form tiny bubbles, thereby creating a microporous structure inside the product. After the injection molding is completed, turn off the casting machine and let the product cool in the mold for a period of time. After cooling, open the mold and take out the molded glove sample.
[0072] 5. Post-processing
[0073] (1) Smoothing treatment:
[0074] Use a polishing machine to polish the surface of the gloves to improve the smoothness and wearing comfort of the gloves.
[0075] (2) UV curing:
[0076] Use UV curing technology to quickly cure the coating to improve production efficiency and coating adhesion. The UV wavelength is 365 nm and the curing time is 10 seconds.
[0077] Example 5: Preparation of modified TPE gloves
[0078] In this embodiment, the material of the TPE gloves is surface modified and micro-foam injection molding technology is used. The specific steps are as follows:
[0079] 1. Drying
[0080] 10 g of the surface-modified WCNFs prepared in Example 1, 100 g of styrene-ethylene / butylene-styrene block copolymer (SEBS), 0.5 g of antioxidant Irganox 1010, and 2 g of black masterbatch were placed in a drying oven and dried at 60° C. for 6 hours to remove any moisture that may be present.
[0081] 2. Material Mixing
[0082] The dried SEBS and surface-modified WCNFs were placed in a high-speed mixer and mixed at 1500 rpm for 8 minutes to ensure that all components were fully dispersed. Irganox 1010 and black masterbatch were then added and mixed for another 8 minutes to ensure that all additives were evenly dispersed.
[0083] 3. Preparation of composite materials
[0084] Put the mixed materials into a twin-screw extruder, set the extrusion parameters, and perform melt extrusion to prepare composite material particles. The extrusion parameters are as follows:
[0085] Barrel temperature: 160°C; screw speed: 100 rpm; extrusion rate: 4 kg / h.
[0086] 4. Injection molding
[0087] (1) Set injection molding parameters:
[0088] Cylinder temperature: 180°C; Mold temperature: 40°C; Injection pressure: 100 MPa; Holding time: 20 seconds; Injection speed: 60 mm / s; Foaming agent: supercritical carbon dioxide ( ), the addition amount is 3% of the weight of the composite material.
[0089] (2) Micro-foam injection molding:
[0090] Same as Example 4.
[0091] 5. Post-processing
[0092] (1) Smoothing treatment:
[0093] Use a polishing machine to polish the surface of the gloves to improve the smoothness and wearing comfort of the gloves.
[0094] (2) UV curing:
[0095] Use UV curing technology to quickly cure the coating, improving production efficiency and coating adhesion. The UV wavelength is 365 nm and the curing time is 15 seconds.
[0096] Example 6: Preparation of modified TPE gloves
[0097] In this embodiment, the material of the TPE gloves is surface modified and micro-foam injection molding technology is used. The specific steps are as follows:
[0098] 1. Drying
[0099] 15 g of the surface-modified WCNFs prepared in Example 1, 100 g of styrene-ethylene / butylene-styrene block copolymer (SEBS), 1 g of antioxidant Irganox 1010, and 1 g of black masterbatch were placed in a drying oven and dried at 80° C. for 4 hours to remove any moisture that may be present.
[0100] 2. Material Mixing
[0101] The dried SEBS and surface-modified WCNFs were placed in a high-speed mixer and mixed at 1000 rpm for 12 minutes to ensure that all components were fully dispersed. Irganox 1010 and black masterbatch were then added and mixed for another 10 minutes to ensure that all additives were evenly dispersed.
[0102] 3. Preparation of composite materials
[0103] Put the mixed materials into a twin-screw extruder, set the extrusion parameters, and perform melt extrusion to prepare composite material particles. The extrusion parameters are as follows:
[0104] Barrel temperature: 180°C; screw speed: 80 rpm; extrusion rate: 5 kg / h.
[0105] 4. Injection molding
[0106] (1) Set injection molding parameters:
[0107] Cylinder temperature: 200°C; Mold temperature: 50°C; Injection pressure: 80 MPa; Holding time: 20 seconds; Injection speed: 50 mm / s; Foaming agent: supercritical carbon dioxide ( ), the addition amount is 2% of the weight of the composite material.
[0108] (2) Micro-foam injection molding:
[0109] Same as Example 4.
[0110] 5. Post-processing
[0111] (1) Smoothing treatment:
[0112] Use a polishing machine to polish the surface of the gloves to improve the smoothness and wearing comfort of the gloves.
[0113] (2) UV curing:
[0114] Use UV curing technology to quickly cure the coating to improve production efficiency and coating adhesion. The UV wavelength is 365 nm and the curing time is 20 seconds.
[0115] Comparative Example 1: Preparation of modified TPE gloves
[0116] In this comparative example, the material of the TPE gloves was surface modified, but the micro-foam injection molding technology was not used. The specific steps are as follows:
[0117] 1. Drying
[0118] 15 g of the surface-modified WCNFs prepared in Example 1, 100 g of styrene-ethylene / butylene-styrene block copolymer (SEBS), 1 g of antioxidant Irganox 1010, and 1 g of black masterbatch were placed in a drying oven and dried at 80° C. for 4 hours to remove any moisture that may be present.
[0119] 2. Material Mixing
[0120] The dried SEBS and surface-modified WCNFs were placed in a high-speed mixer and mixed at 1000 rpm for 12 minutes to ensure that all components were fully dispersed. Irganox 1010 and black masterbatch were then added and mixed for another 10 minutes to ensure that all additives were evenly dispersed.
[0121] 3. Injection molding
[0122] (1) Setting the parameters of the casting machine:
[0123] Cylinder temperature: 180°C; mold temperature: 40°C; injection pressure: 100 MPa; holding time: 15 seconds; injection speed: 80 mm / s;
[0124] (2) Injection molding process:
[0125] Add the mixed material into the hopper of the tape casting machine. The tape casting machine heats the material to 180°C to melt it. The molten material is injected into the mold preheated to 40°C through a nozzle under high pressure, maintaining a certain pressure and time to ensure that the material completely fills the mold and cools to shape. The mold is opened and the molded glove sample is taken out.
[0126] Comparative Example 2: Preparation of unmodified TPE gloves
[0127] The material of the TPE gloves in this comparative example has not been surface modified, but micro-foam injection molding technology is used, and the specific steps are as follows:
[0128] 1. Drying
[0129] 5 g of WCNFs, 100 g of styrene-ethylene / butylene-styrene block copolymer (SEBS), 1 g of silver ion antibacterial agent, 0.5 g of Irganox 1010, 1 g of PEG-100 stearate, and 2 g of black masterbatch were placed in a drying oven and dried at 60 °C for 4 h to remove possible moisture.
[0130] 2. Material Mixing
[0131] Put the dried SEBS and WCNFs into a high-speed mixer and mix them at 1000 rpm for 10 minutes to ensure that all components are fully dispersed. Then add silver ion antibacterial agent, Irganox 1010, PEG-100 stearate, and black masterbatch and continue mixing for 10 minutes to ensure that all additives are evenly dispersed.
[0132] The other steps are the same as in Example 4.
[0133] Example 7: Performance Test
[0134] 1. Sample grouping:
[0135] Control group: ordinary gloves available on the market;
[0136] Experimental Group 1: Unmodified TPE gloves prepared in Comparative Example 2;
[0137] Experimental Group 2: Modified TPE gloves prepared in Comparative Example 1;
[0138] Experimental group 3: modified TPE gloves prepared in Example 4.
[0139] 2. Appearance inspection
[0140] Check the appearance of the gloves to ensure there are no defects, such as bubbles, cracks, etc. Upon inspection, the appearance of the gloves in the four groups was intact without any defects.
[0141] 3. Tensile strength and elongation at break test
[0142] The tensile strength and elongation at break of gloves were measured using a tensile testing machine according to ASTM D638.
[0143] The results are shown in Table 1. The tensile strength and elongation at break of the experimental group are higher than those of the control group, indicating that the mechanical strength of the gloves in the experimental group is better than that of the control group, and experimental group 3 has the highest tensile strength and elongation at break, while the mechanical properties of experimental group 2 are slightly lower than those of experimental group 3, indicating that surface modification and micro-foam injection molding techniques can improve the mechanical strength of gloves.
[0144] Table 1 Tensile strength and elongation at break results
[0145]
[0146] 4. Wear resistance test
[0147] The abrasion resistance of gloves is measured using an abrasion tester according to ASTM D3389.
[0148] The results are shown in Table 2. The wear amount of the experimental groups is lower than that of the control group, indicating that the wear resistance of the experimental groups is better than that of the control group, and experimental group 3 has the lowest wear amount, while the wear resistance of experimental group 2 is slightly higher than that of experimental group 3, indicating that surface modification and micro-foam injection molding technology can improve the wear resistance of gloves.
[0149] Table 2 Wear results
[0150]
[0151] 5. Antibacterial performance test
[0152] The antibacterial properties of gloves were tested using the plate count method. Specifically, each group of glove samples was cut into small pieces and placed in a culture medium containing standard strains (Escherichia coli and Staphylococcus aureus). After incubation for 24 hours, the culture medium was taken for plate count. The antibacterial rate was calculated as follows: Antibacterial rate = (number of colonies in the control group - number of colonies in the experimental group) / number of colonies in the control group × 100%.
[0153] The results are shown in Table 3. The antibacterial rates of the three experimental groups were higher than those of the control group, indicating that the antibacterial properties of the experimental groups were better than those of the control group, and experimental group 3 had the highest antibacterial rate, while the antibacterial rate of experimental group 2 was slightly lower than that of experimental group 3, indicating that surface modification and micro-foam injection molding techniques can improve the antibacterial properties of gloves.
[0154] Table 3 Antibacterial rate results
[0155]
[0156] 6. Antistatic performance test
[0157] The surface resistivity of gloves was measured using a surface resistivity tester. The surface resistivity of gloves was measured according to ASTM D257.
[0158] The results are shown in Table 4. The surface resistivity of the three experimental groups was higher than that of the control group, indicating that the antistatic properties of the experimental groups were better than those of the control group. Experimental group 3 had the highest surface resistivity, while the surface resistivity of experimental group 2 was slightly lower than that of experimental group 3, indicating that surface modification and micro-foam injection molding techniques can improve the antistatic properties of gloves.
[0159] Table 4 Surface resistivity results
[0160]
[0161] 7. Thermal insulation performance test
[0162] The thermal conductivity of the gloves was measured using a thermal conductivity tester. The thermal conductivity of the gloves was measured according to the ASTM C177 standard.
[0163] The results are shown in Table 5. The thermal conductivity of the three experimental groups is lower than that of the control group, indicating that the thermal insulation performance of the experimental groups is better than that of the control group, and experimental group 3 has the lowest thermal conductivity, while the thermal conductivity of experimental group 2 is slightly lower than that of experimental group 3, indicating that surface modification and micro-foam injection molding technology can improve the thermal insulation performance of gloves.
[0164] Table 5 Thermal conductivity results
[0165]
[0166] 8. Long-term stability test
[0167] (1) Thermal aging: Place the glove samples in an oven at 80°C for 7 days, take out the samples, cool them naturally to room temperature, and then perform mechanical property tests.
[0168] (2) Hygrothermal aging: Place the glove samples in a humid and hot environment (temperature 40°C, humidity 90%) for 7 days to test their mechanical properties and functionality. Take out the samples, cool them naturally to room temperature, and then conduct a mechanical property test.
[0169] (3) Ultraviolet aging: The glove samples were exposed to ultraviolet light for 7 days to test their mechanical properties.
[0170] The results are shown in Table 6. After aging treatment, the tensile strength and elongation at break of the experimental group were higher than those of the control group, indicating that the mechanical strength of the gloves in the experimental group was better than that of the control group, and experimental group 3 had the highest tensile strength and elongation at break, while the mechanical properties of experimental group 2 were slightly lower than those of experimental group 3, indicating that surface modification and micro-foam injection molding technology can improve the anti-aging property of gloves and increase the use circumference of gloves.
[0171] Table 6 Tensile strength and elongation at break results
[0172]
[0173] Through the above systematic experiments and tests, the reliability and stability of the synergistic effect of micro-foam injection molding technology and surface modified wood nanocellulose (Modified WCNFs) can be fully verified. These test results will provide scientific data support to ensure that the produced TPE gloves achieve the expected results in mechanical properties, antibacterial properties, antistatic properties, density, thermal insulation properties and long-term stability. This will not only help improve the quality and market competitiveness of the product, but also provide valuable data reference for future research and development and improvement.
[0174] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A TPE glove, characterized in that: The components of the TPE gloves include, by weight: 100 parts of a base material, 5 parts of bio-based nanocellulose, 0.5 parts of an antioxidant, and 2 parts of a masterbatch; the base material is SEBS; the antioxidant is Irganox 1010; The bio-based nanocellulose is wood cellulose nanocellulose WCNFs; the wood cellulose nanocellulose WCNFs are specifically surface-modified WCNFs, and the preparation steps are: (1) Take 5 g of 1 wt% WCNFs suspension and 100 mL of 1 wt% silver ion solution and stir them on a magnetic stirrer for 1 hour, add 10 mL of 1 M hydrochloric acid solution to adjust the pH to 4-5, and continue stirring for 1 hour to load silver ions on the surface of WCNFs; then centrifuge at 8000 rpm for 10 minutes to remove the supernatant, wash the precipitate with deionized water and 95% ethanol three times, and redisperse it in 100 mL of deionized water to obtain WCNFs loaded with silver nanoparticles; (2) 5 g of the WCNFs loaded with silver nanoparticles at a concentration of 1 wt% were stirred with 100 mL of a polypyrrole solution at a concentration of 1 wt% and 10 mL of 0.1 M ammonium persulfate on a magnetic stirrer for 2 hours to initiate a polymerization reaction so that the conductive polymer was coated on the surface of the WCNFs; then, the mixture was centrifuged at 8000 rpm for 10 minutes to remove the supernatant, and the precipitate was washed three times with deionized water and 95% ethanol, and then redispersed in 100 mL of deionized water to obtain modified WCNFs; (3) placing the modified WCNFs in an oven at 60° C. and drying them for 24 hours until they are completely dry to obtain surface-modified WCNFs; The method for preparing the TPE gloves comprises the following steps: (1) SEBS, surface-modified WCNFs, Irganox 1010, and masterbatch raw materials were dried at 60 °C for 4 h to remove excess water; (2) Place the dried SEBS and surface-modified WCNF into a high-speed mixer and mix at 1000 rpm for 10 minutes. Add Irganox 1010 and masterbatch and continue mixing for 10 minutes. (3) Melting and extruding the uniformly mixed components to prepare composite material particles; the extrusion parameters are as follows: barrel temperature: 180°C; screw speed: 100 rpm; extrusion rate: 5 kg / h; (4) The composite material particles are subjected to micro-foam injection molding technology to prepare glove samples; the parameters of the micro-foam injection molding technology are set as follows: barrel temperature: 180°C; mold temperature: 40°C; injection pressure: 100 MPa; holding time: 15 seconds; injection speed: 80 mm / s; foaming agent: supercritical carbon dioxide, the addition amount of which is 1% of the weight of the composite material; (5) The glove sample is smoothed and cured by ultraviolet light to obtain a TPE glove; the wavelength of the ultraviolet light is 365 nm and the curing time is 10 seconds.
Citation Information
Patent Citations
Preparation method of polyaniline coated silver-loaded nano microcrystalline cellulose-based conductive ink
CN110041762A
Fiber latex composite material as well as preparation method and application thereof
CN111410776A